New states of matter with fine-tuned interactions: quantum droplets and dipolar supersolids. (23rd December 2020) - Böttcher, Fabian; Schmidt, Jan-Niklas; Hertkorn, Jens; Ng, Kevin S H; Graham, Sean D; Guo, Mingyang; Langen, Tim; Pfau, Tilman
Abstract: Quantum fluctuations can stabilize Bose–Einstein condensates (BEC) against the mean-field collapse. Stabilization of the condensate has been observed in quantum degenerate Bose–Bose mixtures and dipolar BECs. The fine-tuning of the interatomic interactions can lead to the emergence of two new states of matter: liquid-like self-bound quantum droplets and supersolid crystals formed from these droplets. We review the properties of these exotic states of matter and summarize the experimental progress made using dipolar quantum gases and Bose–Bose mixtures. We conclude with an outline of important open questions that could be addressed in the future.